HIV Programs for Sex Workers : Lessons and Challenges for Developing and Delivering Programs - Wilson, David (Public Library of Science, 2015)
There is evidence that HIV prevention programs for sex workers, especially female sex workers, are cost-effective in several contexts, including many western countries, Thailand, India, the Democratic Republic of Congo, Kenya, and Zimbabwe. The evidence that sex worker HIV prevention programs work must not inspire complacency but rather a renewed effort to expand, intensify, and maximize their impact. The PLOS Collection “Focus on Delivery and Scale: Achieving HIV Impact with Sex Workers” highlights major challenges to scaling-up sex worker HIV prevention programs, noting the following: sex worker HIV prevention programs are insufficiently guided by understanding of epidemic transmission dynamics, situation analyses, and programmatic mapping; sex worker HIV and sexually transmitted infection services receive limited domestic financing in many countries; many sex worker HIV prevention programs are inadequately codified to ensure consistency and quality; and many sex worker HIV prevention programs have not evolved adequately to address informal sex workers, male and transgender sex workers, and mobile- and internet-based sex workers. Based on the wider collection of papers, this article presents three major clusters of recommendations: (i) HIV programs focused on sex workers should be prioritized, developed, and implemented based on robust evidence; (ii) national political will and increased funding are needed to increase coverage of effective sex worker HIV prevention programs in low and middle income countries; and (iii) comprehensive, integrated, and rapidly evolving HIV programs are needed to ensure equitable access to health services for individuals involved in all forms of sex work.